GAMBARAN STATUS GIZI SISWA SEKOLAH MENENGAH PERTAMA (SMP) DI KUTA, BALI - I Gusti Ngurah Juniartha; Ni Putu Emy Darmayanti (Coping: Community of Publishing in Nursing, 2020)
Adolescents are an aggregate that is prone to experiencing malnutrition or overweight problems. Generally, they do physical activity higher than other aggregates, so they require more nutritional fulfillment. However, the excessive nutrition intake can also occur due to poor eating habits so that the amount of energy input is greater than the expended energy. The aim of this study was to describe the nutritional status of adolescent students. This is a quantitative research with analytic descriptive design using purposive sampling technique on 185 junior high school students in Kuta, Bali. Nutritional status data is obtained by measuring the height of the body using microtoise tool and body weight of the respondents using a mechanical weighing scale. Nutritional status is classified based on the BMI/age z-score table value for children aged 5-18 years from the 2011 Ministry of Health of Indonesia guidelines. The results of data analysis show that the nutritional status category of junior high school students involved as respondents is the majority in the category of normal nutritional status, namely 89 people (48.10%). However, there are still 6 students (3.24%) who have obese status. An efforts were need to be made to maintain the nutritional status of students consistently and in synergy from various parties (parents, schools, and the government).